Proteomic and metabolomic analysis of minimax and Williams 82 soybeans grown under two different conditions. Issue 6 (3rd August 2017) - John, K. M. Maria; Khan, Farooq; Luthria, Davanand L.; Matthews, Benjamin; Garrett, Wesley M.; Natarajan, Savithiry
Abstract: MiniMax was developed as a model soybean for research because of its small stature, limited planting space, and rapid generation time. In the present study, the proteins, isoflavones, and fatty acid methyl esters (FAMEs) were compared between dwarf (MiniMax) and commercially cultivated (Williams 82) soybean genotypes under two growing conditions (greenhouse and field). The protein profile of the soybean extracts by 2D‐PAGE showed at least 16 of 716 spots that were differently expressed in MiniMax and Williams 82. These spots were primarily six proteins namely, seed biotin, β‐conglycinin, glycinin, seed‐maturation protein, glutathione‐S‐transferase, and sucrose binding protein. In both genotypes, higher content of isoflavone aglycones was observed in greenhouse grown samples as compared to the field grown samples. However, only field grown Willams 82 had higher levels of FAMEs as compared to other three groups. This study shows that both growing conditions and cultivars significantly influence the compositional content of metabolites. Practical applications: The global demand of soybean and its products has increased due to its high protein and isoflavones content. Researchers are actively developing new genotypes with improved yields, greater drought and disease tolerance, and reduced growth time. MiniMax, a dwarf genotype of soybean showed early flowering, seed setting, and maturation traits due to its multiple dwarfing genes. This characteristic feature enables researchers to study effects of various treatments on soybean in a shorter period with multiple replications in a single growing season.